Planning to Build A Park and Ride in The Town Square of Bekasi - Muhammad Isradi; Rana Reza Vahira (NAROTAMA UNIVERSITY, Indonesia)
The need for transportation has now become a very meeting thing for residents of a city. Because transportation is a very important means of smoothing the economy of a region. Along with the growing economy of residents in an area, the number of owners and users of private vehicles has also increased rapidly. That needs to be balanced with supporting transportation support facilities. For that we need a solution to reduce congestion by maximizing the benefits of public transportation such as commuter line trains. One thing that can be done is the construction of a Park and ride building as a transportation support facility at Bekasi Station, Bekasi City. To plan a Park and ride building some data is needed. Data obtained from field surveys, namely surveys to obtain the demand value for the arrival of vehicles. The survey was conducted by counting the number of vehicles leaving and entering the Bekasi station parking lot which is divided into two zones, namely the northern zone and the southern zone. The survey was carried out at 06.00 – 21.00 WIB. In the results of data processing using excel, it is obtained the characteristics of Park and ride facilities users and also the number of users demand for park and ride facilities for motorbikes is 676, while for cars is 107 vehicles. of the total demand, a park and ride building is planned to accommodate 1000 motorbikes and 100 cars with 3 floors.